326 PARASYMPATHETIC INNERVATION MAY MEDIATE THE EFFECT OF AGE AND GENDER ON BODY FAT DISTRIBUTION IN HUMANS. (1st January 2006) - Tong, J.; Utzschneider, K. M.; Carr, D. B.; Hull, R. L.; Udayasankar, J.; Gerchman, F.; Zraika, S.; Knopp, R. H.; Kahn, S. E.
Abstract : Objective: Pancreatic polypeptide (PP) is a 36-amino acid peptide produced by the F-cells of the pancreas, the plasma concentration of which has been used as a marker of parasympathetic activity. Recent work in rodents suggests that both sympathetic and parasympathetic input to adipose tissue may regulate its endocrine function and play a role in intra-abdominal fat (IAF) accumulation. We hypothesized that in humans parasympathetic activity mediates IAF accumulation and thereby insulin resistance. Research Design and Methods: To test this hypothesis, we measured PP levels in 177 non-diabetic, healthy subjects (75 M/102 F; age 32-75 y). IAF and subcutaneous fat (SCF) areas were measured by CT scan. The insulin sensitivity index (SI ) was quantified using Bergman's minimal model from the results of a tolbutamide-modified frequently sampled intravenous glucose tolerance test. Results: PP levels were higher in men than in women (96.2 ± 72.2 vs 76.1 ± 55.0 pg/mL, mean ± SD, p = .037), as was IAF area (124.7 ± 67.4 vs 83.0 ± 57.7 cm 2, p < .001). However, SCF was higher in women than in men (243.0 ± 133.1 vs 184.0 ± 87.8 cm 2, p = .001). PP levels were positively associated with age (β = 0.03, p < .01). While PP levels were significantly associated with IAF (β = 0.01, p = .031), they were not associated with SCF (β = 0.001, p = .829). The association between PP and IAF disappeared after adjusting for age or gender. SI was negatively associated with PP levels (β = -0.002, p = .026) and IAF area (β = -0.006, p < .001). The association between SI and PP disappeared after adjusting for IAF. Conclusion: In humans, parasympathetic innervation may be mediating the effect of age and gender on IAF accumulation, but not SCF accumulation.